Quality system for a testing and calibration laboratory - 326396 Ng, Chai Peng (Sekudai : UTM, 1994)
Quality is now regarded as the principal means of survival. The assurance of the quality has become increasingly important as a result of the growing demands of quality product by the public coupled with global comptetion among manufacturers. The final "product" of a laboratory is test data. Provision adn the use of unreliable or incorrect data lead to wong decisions usually with cost consequences. Therefore, today, demands for quality in testing and calibration services has resulted in the world-wide acceptance of the ISO/IEC Guide 25. In this dissertation, the basic concept of quality assurance system is presented. A proposed quality assurance system is drafted based on the ISO/IEC Guide 25 to be applied at Metrology Laboratory, Universiti Teknologi Malaysia. There are six selected clases; namely quality system, accomodation & environment, equipment & reference material, calibration & test methods, handling of calibration & test items and records are prepared. The utmost point is that the quality system proposal should be practically materialized if the laboratory would like to operate under the SAMM accreditation.